Disturbance observer based discrete PI control system with back-calculation antiwindup technique for improvement transient performance of PMSM - Sarsembayev Б.К. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
In this paper discrete-time field-oriented control (FOC) for PMSM speed control has been proposed. The cascade structure of the discrete-time PI-PI control system with tracking back-calculation anti-windup scheme. The novel anti-windup scheme for both loops has been adopted. Windup phenomena in traditional PI controllers have greater negative effects on the transient performance in engineering applications such as PMSM. In the real-time experiments, the proposed control system achieves less speed errors and faster response. The experimental results have proved the feasibility of the proposed control scheme.